Innovative nanocomposite comprising of ZrO2, MnCO3, and CdCO3 for superior crystal violet dye adsorption: synthesis, characterization, and regeneration insights - Nada S. Al-Kadhi; Ehab A. Abdelrahman; Fowzia S. Alamro; Fawaz A. Saad; Doaa S. Al-Raimi (Scientific Reports)
Abstract Crystal violet dye, widely used in industries, poses environmental and human health hazards due to its persistence and toxicity. Effective removal methods are critical to mitigate these impacts. This study presents the synthesis of a novel ZrO2@MnCO3@CdCO3 nanocomposite for the efficient removal of crystal violet dye from aqueous solutions. The nanocomposite was synthesized using a precipitation method and characterized using XRD, SEM, EDX, and BET surface area analysis. Adsorption experiments were conducted under various conditions, including pH, contact time, concentration, and temperature. The ZrO2@MnCO3@CdCO3 nanocomposite exhibited a mesoporous structure (22.38 m2/g surface area, 0.0935 cm3/g total pore volume, and 8.79 nm average pore size) and an average crystallite size of 76.30 nm. The maximum adsorption capacity for crystal violet dye was 179.52 mg/g, following pseudo-second-order kinetics and the Langmuir isotherm. Thermodynamic studies revealed an exothermic, physical, and spontaneous adsorption process. Regeneration experiments demonstrated high reusability with desorption efficiency reaching 99.67% over five cycles.